2008
DOI: 10.1152/ajplung.00377.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic provenance of STAT3 and PY-STAT3 in the endolysosomal compartments in pulmonary arterial endothelial and smooth muscle cells: implications in pulmonary arterial hypertension

Abstract: PB. Cytoplasmic provenance of STAT3 and PY-STAT3 in the endolysosomal compartments in pulmonary arterial endothelial and smooth muscle cells: implications in pulmonary arterial hypertension. Am J Physiol Lung Cell Mol Physiol 294: L449-L468, 2008. First published December 14, 2007 doi:10.1152/ajplung.00377.2007.-Lung vascular lesions in pulmonary arterial hypertension (PAH) are characterized by enlarged, vacuolated ("megalocytotic") pulmonary arterial endothelial (PAEC) and smooth muscle cells (PASMC). We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…A single exposure of confluent bovine PAEC cultures to MCTP for as short a time as 2 min leads to apoptosis of a small subset of cells with the development of marked megalocytosis of cells in the surviving, but still confluent, cell sheet 18 -24 h later (18,38,48,49,68, 73). As with the in vivo observations (27, 34 -36), the cell culture studies showed dramatic increases in cell size, in Golgi stacks, and in the endoplasmic reticulum; increased DNA synthesis; and a unique premitotic cell cycle arrest despite the continued DNA synthesis resulting in hyperploidy of the affected cells (18,25,33,36,(39)(40)(41)48,49,55,57,61,66; reviewed in Refs. 53,54).…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…A single exposure of confluent bovine PAEC cultures to MCTP for as short a time as 2 min leads to apoptosis of a small subset of cells with the development of marked megalocytosis of cells in the surviving, but still confluent, cell sheet 18 -24 h later (18,38,48,49,68, 73). As with the in vivo observations (27, 34 -36), the cell culture studies showed dramatic increases in cell size, in Golgi stacks, and in the endoplasmic reticulum; increased DNA synthesis; and a unique premitotic cell cycle arrest despite the continued DNA synthesis resulting in hyperploidy of the affected cells (18,25,33,36,(39)(40)(41)48,49,55,57,61,66; reviewed in Refs. 53,54).…”
mentioning
confidence: 58%
“…Neointima development, thrombotic obliteration of arterial lumen, and development of plexiform lesions, reminiscent of human PAH, have also been reported with MCT when combined with partial pneumonectomy (44, 65 and citations therein). Additionally, perivascular/adventitial infiltrative cells and their cytokine contributions (such as IL-6) and transcription factors activated by such cytokines (STAT3 and NF-B) have been posited as contributory factors in the development of disease in this model (2,14,15,30,41,64).Over the last two decades bovine PAECs and PASMCs in culture exposed to MCTP have been used as experimental models to investigate some of the cellular, subcellular, and biochemical changes elicited by MCTP (18,25,26,30,[38][39][40][41][42]48,49,[53][54][55]57,61,66). A single exposure of confluent bovine PAEC cultures to MCTP for as short a time as 2 min leads to apoptosis of a small subset of cells with the development of marked megalocytosis of cells in the surviving, but still confluent, cell sheet 18 -24 h later (18,38,48,49,68, 73).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, evidence has emerged that phosphorylation of STAT3 does not necessarily lead to nuclear translocation [21,23]. It is therefore necessary to demonstrate the nuclear accumulation of PY-STAT3 when studying PY-STAT3-dependent gene expression.…”
Section: Nuclear Appearance Of Py-stat3mentioning
confidence: 99%